EFEKTIFITAS AROMATERAPI LAVENDER TERHADAP KUALITAS TIDUR IBU POSTPARTUM - Diva ' de Laura; Misrawati ' '; Rismadefi ' Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research was to identify the effect of lavender aromatherapy for postpartum mother sleep quality. Design of this study was quasy experiment with non-equivalent control group design. The data was conducted in Puskesmas Sidomulyo area with 34 samples which divided into 17 as experimental group and 17 as a control group based on inclusions criteria using purposive sampling. Experimental group was given lavender aromatherapy every night before sleep for 5-10 minutes in seven days, meanwhile control group were not. Sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI). The univariate analysis was conducted to showed frequency distribution and bivariate analysis was conducted by independent sample T-test and dependent sample T-test. Result showed that mean of postpartum mother sleep quality after given lavender aromatherapy in experiment group was 4.71 and mean of postpartum mother sleep quality without given lavender aromatherapy in control group was 8.71. The statistic showed p value (0.000) < alpha (0.05) which means that lavender aromatherapy effective for postpartum mother sleep quality and recommended to be applied in nursing intervention for increase postpartum mother sleep quality. Keywords: Lavender aromatherapy, postpartum, Pittsburgh Sleep Quality Index (PSQI), sleep